Road Traffic Injury as a Major Public Health Issue in the Kingdom of Saudi Arabia: A Review - DeNicola, Erica; Aburizaize, Omar S.; Siddique, Azhar; Khwaja, Haider; Carpenter, David O. (Frontiers in Public Health, 2016)
Injury was the largest single cause of disability-adjusted life years (DALYs) and death in the Kingdom of Saudi Arabia I 2013. The vast majority of injury-related fatalities are deaths caused by road traffic. Measures to control this serious public health issue, which has significant consequences for both Saudi families and the Saudi economy as a whole, have been underway for years but with little success. Most attempts at intervening revolve around attempts for enforce stricter traffic laws and by installing automated traffic monitoring systems that will catch law breakers on camera and issue tickets and fines. While there has been much research on various factors that play a role in the high rate of road traffic injury in The Kingdom (e.g., driver behavior, animal collisions, disobeying traffic and pedestrian signals, environmental elements), virtually no attention has been given to examining why Saudi drivers behave the way that they do. This review provides a thorough account of the present situation in Saudi Arabia and discusses how health behavior theory can be used to gain a better understanding of driver behavior.